2010
DOI: 10.1111/j.1749-818x.2010.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatics: From Theory to Experiment and Back Again

Abstract: This paper reviews some cases in which the collaboration of theoretical pragmaticians and psychologists of language has been most fruitful for all parties. Linguists have benefited from experimental data confirming the psychological validity of their observations and providing theorycritical evidence in cases beyond the reach of reflective intuition, while psychologists have benefited from having a wealth of linguistic phenomena to study as well as multiple theories furnished by semantics and pragmatics. Focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Although our own study is not directly concerned with this issue, the results that have been obtained in these studies motivate our own hypotheses and design. We will therefore briefly review some of the main findings (see also Katsos and Cummins, 2010).…”
Section: The Role Of Processing Resultsmentioning
confidence: 99%
“…Although our own study is not directly concerned with this issue, the results that have been obtained in these studies motivate our own hypotheses and design. We will therefore briefly review some of the main findings (see also Katsos and Cummins, 2010).…”
Section: The Role Of Processing Resultsmentioning
confidence: 99%
“…Scalar implicature is a pragmatic phenomenon wherein a weak term such as ‘some’ is taken to mean that a stronger term is not true (e.g., ‘some’ is interpreted as not all ) [9,11,18]. ‘Some’ thus has two interpretations: a purely semantic interpretation ( at least one ) and a pragmatic interpretation ( at least one but not all ).…”
Section: Introductionmentioning
confidence: 99%
“…This may mean that SOME is only interpreted to mean the negation of another element in a scale if that element of the scale is an expected lexical alternative in the context-in other words, SOME can only be interpreted as NOT ALL if ALL was also available in the context, and likewise SOME can only be interpreted as NOT MOST if MOST was also available in the context. Support for this notion comes from both introspective and empirical data regarding boundedness (Breheny et al, 2006;Katsos & Cummins, 2010). Such data have shown that SOME is more likely to be interpreted as NOT ALL when uttered as a response to a question where ALL would have been a relevant response (an upper-bound context), as in (7), than to a sentence where ALL would not have been relevant (a lower-bound context), as in (8); examples are from Katsos & Cummins (2010).…”
Section: Reaction Timesmentioning
confidence: 99%
“…Support for this notion comes from both introspective and empirical data regarding boundedness (Breheny et al, 2006;Katsos & Cummins, 2010). Such data have shown that SOME is more likely to be interpreted as NOT ALL when uttered as a response to a question where ALL would have been a relevant response (an upper-bound context), as in (7), than to a sentence where ALL would not have been relevant (a lower-bound context), as in (8); examples are from Katsos & Cummins (2010).…”
Section: Reaction Timesmentioning
confidence: 99%